Metabolomic studies reveal and validate potential biomarkers of diabetic retinopathy in two Chinese datasets with type 2 diabetes: a cross-sectional study - Xingchen Zhou; Guixue Hou; Xin Wang; Zhaoyi Peng; Xiaoming Yin; Jing Yang; Shan Wang; Yayi He; Yue Wang; Jing Sui; Wei Qiang; Hui Guo; et al. (Cardiovascular Diabetology)
Abstract Background Diabetic retinopathy (DR) is a major microvascular complication of diabetes mellitus and causes vision impairment and blindness. The presence of major risk factors for DR, such as high levels of HbA1c, does not predict all DR pathogenesis in the clinic, which suggests that uncovering the underlying mechanisms and identifying novel markers are needed. Previous evidence has shown that the serum metabolic signature of DR is unique and detectable compared with that of diabetes mellitus (DM). Here, we aimed to identify serum metabolites as reliable biomarkers for the presence of DR in type 2 DM (T2DM) patients. Methods We performed untargeted and targeted metabolomic studies using liquid chromatography‒mass spectrometry (LC‒MS) and multiple reaction monitoring (MRM) methods on the serum samples of T2DM patients. For the discovery dataset, 39 DR patients and 39 non-DR (NDR) patients were included. For the validation dataset, 95 DR patients and 95 non-DR (NDR) patients were included. Receiver operating characteristic curve analysis was performed to evaluate the discriminating power of the metabolites. Binary logistic regression models were fit to evaluate the associations of metabolite peak areas or neurotransmitter concentrations with the presence of DR and adjusted for known risk factors. Results A total of 7123 metabolites were tested. The 39 DR patients had a mean age of 56 years with an average diabetes duration of 12 years, and the 39 NDR patients had a mean age of 57 years with an average diabetes duration of 11 years. Nine serum candidate markers were further identified. Six out of nine markers were associated with DR after we adjusted for covariates, including blood pressure, HbA1c, diabetes duration, fasting blood glucose, triglyceride, eGFR etc. Among them, eicosapentaenoic acid (EPA) and L-tyrosine were validated in an independent, risk factor-matched sample set. The serum L-tyrosine concentration was decreased in DR group by 47% (-0.22 ± 0.87 vs. 0.48 ± 1.05, P < 0.001), of which the cutoff value was 0.10 mg/ml, with 86% sensitivity and 40% specificity (AUC = 0.62, 95% CI = 0.54–0.70, P = 0.005). Conclusions Low levels of circulating L-Tyrosine indicate retinopathy occurrence in T2DM population.